2021
DOI: 10.6007/ijarbss/v11-i2/9205
|View full text |Cite
|
Sign up to set email alerts
|

Teaching in the Time of Covid-19: The Challenges Faced By Teachers in Initiating Online Class Sessions

Abstract: The severity of COVID-19 has called the education world to transition into cyberspace education to support the continuity of teaching and learning. The stages of Movement Control Order (MCO), Conditional MCO, and Restricted MCO have resulted in prolonged closure of schools within affected areas. In the Guidelines of Teaching and Learning (T&L) during MCO,' the Ministry of Education, Malaysia (MoE) has come up with several initiatives for the continuation of education, which include adopting the synchronous and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Teachers had to know the whole online teaching system to cope with this new situation, even though some had never taught online before the pandemic. This result follows the results of Izhar et al (2021), who studied most of the participants and declared that preparing lessons to fit an online teaching platform is time-consuming and requires extra effort from the teachers. Akbulut et al (2020) added that even teachers with previous experience in online teachings, such as blended learning, stated that such lessons require excessive preparation time.…”
Section: B Online Learning / Personal Reflectionsupporting
confidence: 86%
“…Teachers had to know the whole online teaching system to cope with this new situation, even though some had never taught online before the pandemic. This result follows the results of Izhar et al (2021), who studied most of the participants and declared that preparing lessons to fit an online teaching platform is time-consuming and requires extra effort from the teachers. Akbulut et al (2020) added that even teachers with previous experience in online teachings, such as blended learning, stated that such lessons require excessive preparation time.…”
Section: B Online Learning / Personal Reflectionsupporting
confidence: 86%
“…Even though the instructors had limited practical experience using online platforms for educational purposes, they had to proceed with online teaching and adapt to using those necessary platforms without sufficient time to practice them (Izhar et al, 2021). Huang (2020) also reported that university instructors had to be familiar with online education platforms in a short time in response to COVID-19.…”
Section: Instructors' Struggles Of Adaptation To New Pedagogymentioning
confidence: 99%
“…Some previous researchers investigated a similar topic. Izhar et al (2021) investigated the role of online learning and the goal of education. Ty found that online learning can implement information and communication technologies in the educational sector (Izhar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Izhar et al (2021) investigated the role of online learning and the goal of education. Ty found that online learning can implement information and communication technologies in the educational sector (Izhar et al, 2021). For online learning, teachers and students can interact directly in the classroom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation